RANCANG BANGUN MEDIA PELAYANAN UMUM DESK INFO DI PENGADILAN TINGGI AGAMA PEKANBARU - Zarnelly -; Della Adelia (IIB Darmajaya, 2014)
Pengadilan Tinggi Agama (PTA) Pekanbaru are institutions in services that require and provide good service, fast and accurate for the sake of the best services. However, the applicant information service for PTA Pekanbaru very unsatisfactory because it does not routinely so that data collection is not known how the improvement of performance such as satisfaction with the services provided. This becomes a problem because the Supreme Court at any time will make an assessment. In addition to conference PA PTA Pekanbaru legal difficulties in reporting the number of visitors each month and year information and frequent delays. To overcome these problems, the solutions given in the form of web-based Info Desk applications that support the performance and service of the PTA Pekanbaru. The method used in establishing the method Prototype Info Desk, and using tools UML (Unified Modelling Language) which is a tool of object-based design method, namely OOAD (Object Oriented Analysis Design). With the Info Desk application can improve the performance of the service at the PTA Pekanbaru, help alleviate the Information Desk attendant jobs, and help PA Selat Panjang, PA Pangkalan Kerinci and PA Tembilahan to provide information to the PTA table reports Pekanbaru.Keywords: Desk Info, OOAD, Prototype, WEB.